Refilosofi kebudayaan : pergeseran pascastruktural - Arif, Syaiful, 1981- (Jogjakarta : Ar-Ruzz Media, 2010)
Philosophy of culture.
Includes bibliographical references (p. 345-353) and index.
Keywords: Culture -- Philosophy